1997
DOI: 10.1002/mds.870120309
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and motor evoked potentials in multiple system atrophy: A comparative study with Parkinson's disease

Abstract: Somatosensory evoked potentials (SEPs) to median nerve stimulation and motor evoked potentials to transcranial magnetic stimulation (TMS) of the motor cortex were studied in 15 patients with multiple system atrophy (MSA) and compared with matched groups of 20 patients with idiopathic Parkinson's disease (PD) and of 20 normal controls (NCs). No SEP latency or amplitude abnormalities were observed, and, in particular, the frontal N30 component was not significantly depressed. No differences in TMS threshold for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 30 publications
1
33
1
2
Order By: Relevance
“…As previously reported, 4,14,15 there was no significant difference between patients and control subjects in either the threshold for eliciting EMG responses or their amplitude, but the suppression of test MEPs at short ISIs was significantly impaired in patients.…”
Section: Discussionsupporting
confidence: 64%
“…As previously reported, 4,14,15 there was no significant difference between patients and control subjects in either the threshold for eliciting EMG responses or their amplitude, but the suppression of test MEPs at short ISIs was significantly impaired in patients.…”
Section: Discussionsupporting
confidence: 64%
“…Previous pathological studies have demonstrated more frequent and extensive involvement of the pyramidal tract than that observed at clinical examination in MSA [4][5][6]9], and the level was similar to that of ALS. Despite previous findings of extensive pathological involvement in MSA, it has been noted that it is more difficult to detect pyramidal tract degeneration in MSA by clinical examinations or electrophysiological techniques (such as central motor nerve conduction study) compared with evaluations of degeneration in ALS patients [9][10][11]. These discrepancies may be explained by the size of the neurons and axons which degenerate in MSA.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, pyramidal signs are thought to be less important in diagnosis than the symptoms seen in the other systems. In addition, electrophysiological or magnetic measures to monitor central motor conduction have not been able to detect pyramidal tract degeneration in MSA [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Some sensory systems may also be involved by MSA. However, controversial results have been reported on somatosensory evoked potentials (SEPs) in MSA patients [1,2]. In one study no SEP abnormalities were observed [1], and the other study reported that cortical SEP abnormalities were found in 37% of the MSA patients [2].…”
Section: Introductionmentioning
confidence: 97%